Pragmatic modernism - Schoenbach, Lisi. (New York ; Oxford : Oxford University Press, 2012)
'Pragmatic Modernism' traces an alternative strain of modernism influenced by pragmatist philosophy and characterized by its commitment to gradualism, continuity, and habit rather than spectacular events and radical rupture.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Modernism (Literature); American literature -- 20th century -- History and criticism; American literature -- 19th century -- History and criticism; James, Henry, -- 1843-1916 -- Philosophy; Stein, Gertrude, -- 1874-1946 -- Philosophy; Modernism (Aesthetics); Pragmatism; Habit (Philosophy); Social change -- Philosophy